2019
DOI: 10.5530/pj.2019.11.73
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-psoriatic Potential of the Fruit Rind of Punica granatum L.

Abstract: Background: Pomegranate (Punica granatum L.) is universally known for its therapeutic properties due to its potential bioactive compounds. However, there is no established scientific study on antipsoriatic activity of pomegranate fruit rind. The aim of the study is to evaluate the anti-psoriatic activity of the isolated compounds and the extract from the fruit rind of P. granatum. In our previous study, the isolated compounds were evaluated for antioxidant potential. In continuation to the previous investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…The condition is due to the loss of function of TYMP gene following homozygous mutations c.1283 G > A, and c.1284 T > A, as well as mutations in DNA polymerase subunit gamma (POLG) and ribonucleotide reductase regulatory TP53 inducible subunit M2B (RRM2B) genes that lead to TYMP deficiency [ 252 , 253 , 254 ]. Interestingly, increased TYMP expression has been reported in cases of local inflammations such as rheumatoid arthritis and psoriasis, suggesting its plausible causal link with stress conditions such as hypoxia in the tumor microenvironment [ 255 , 256 ]. Indeed, TYMP overexpression may promote adaptive responses mediated by the hypoxia-inducible factor (HIF-1) pathway that prevents hypoxia-induced apoptosis that is triggered upon continuous chemotherapy [ 229 , 242 , 257 ].…”
Section: Mechanism Of Resistance By Key 5-fluorouracil Enzymesmentioning
confidence: 99%
“…The condition is due to the loss of function of TYMP gene following homozygous mutations c.1283 G > A, and c.1284 T > A, as well as mutations in DNA polymerase subunit gamma (POLG) and ribonucleotide reductase regulatory TP53 inducible subunit M2B (RRM2B) genes that lead to TYMP deficiency [ 252 , 253 , 254 ]. Interestingly, increased TYMP expression has been reported in cases of local inflammations such as rheumatoid arthritis and psoriasis, suggesting its plausible causal link with stress conditions such as hypoxia in the tumor microenvironment [ 255 , 256 ]. Indeed, TYMP overexpression may promote adaptive responses mediated by the hypoxia-inducible factor (HIF-1) pathway that prevents hypoxia-induced apoptosis that is triggered upon continuous chemotherapy [ 229 , 242 , 257 ].…”
Section: Mechanism Of Resistance By Key 5-fluorouracil Enzymesmentioning
confidence: 99%
“…Sun, Tao, et al (2017) reported DPPH radical inhibition values close to 90% at a concentration of 40 ppm using three separate purified compounds (ellagic acid, punicalin, and punicalagin). On the other hand, Jacob et al (2018) used the ABTS method to assess the antioxidant potential of two distilled pomegranate peel compounds (punicalagin and punicalin) at a concentration of 200 ppm, with a 100% inhibition percentage. Aguilar‐Zárate et al (2017) tested the antioxidant activity of distilled punicalagin using two methodologies (DPPH and ABTS), reporting a 50% inhibitory concentration with concentrations of 109 and 151 ppm, respectively.…”
Section: The Antioxidant Capacity Of Pppmentioning
confidence: 99%
“…Natural products have proven to be alternative and potential sources of synthetic drugs. Studies have shown that crude extracts or purifed chemical constituents of various medicinal plants are often more efective than synthetic antioxidants [6]. P. granatum (pomegranate) has been widely used in the food and pharmaceutical industries for a variety of applications and as a source of antioxidants to combat autoxidation-induced pathologies [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its nutritional benefts, the fruit is used empirically for the treatment of various diseases, such as acidosis, dysentery, microbial infections, parasitic infections, hemorrhage, and respiratory pathologies [9,11]. Te pharmacological properties of pomegranate have a long history, and recent decades have seen a growing interest in its therapeutic efects [6].…”
Section: Introductionmentioning
confidence: 99%